Lateral Hypothalamus as a Motivation-Cognition Interface in the Control of Feeding Behavior - Petrovich, Gorica D. (Frontiers in Systems Neuroscience, 2018)
Converging evidence for an essential function of the lateral hypothalamus (LHA) in the control of feeding behavior has been accumulating since the classic work conducted almost eighty years ago. The LHA is also important in reward and reinforcement processes and behavioral state control. A unifying function for the LHA across these processes has not been fully established. Nonetheless, it is considered to integrate motivation with behavior. More recent work has demonstrated that the LHA is also required when cognitive processes, such as associative learning and memory control feeding behavior, suggesting it may serve as a motivation-cognition interface. Structurally, the LHA is well positioned within the cerebral hemisphere, with its extensive connectional network across the forebrain-brainstem axis, to link motivational and behavioral systems with cognitive processes. Studies that examined how learned cues control food seeking and consumption have implicated the LHA, but due to methodological limitations could not determine whether it underlies motivation, learning, or the integration of these processes. Furthermore, the identification of specific substrates has been limited by the LHA’s extraordinary complexity and heterogeneity. Recent methodological advancements with chemo-and opto-genetic approaches have enabled unprecedented specificity in interrogations of distinct neurons and their pathways in behaving animals, including manipulations during temporally distinct events. These approaches have revealed novel insights about the LHA structure and function. Recent findings that the GABA LHA neurons control feeding and food-reward learning and memory will be reviewed together with past work within the context of the LHA function as an interface between cognition and motivation.